Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1969
DOI: 10.4095/103337
|View full text |Cite
|
Sign up to set email alerts
|

Retreat of the last ice sheet from the maritime provinces, Gulf of St Lawrence Region

Abstract: The popular concept of overriding Laurentide ice (Labradorean sector) in the Maritime ProvincPs - Gulf of St. Lawrence region is examined in terms of regional ice-flow patterns and other supporting data - and is found wanting. Are interpretation of the data, the glacial lineations and other features presents a picture of localized, more or less radial outflow from certain upland and lowland areas. The pattern of ice-flow features and end moraines is shown to r e late to a rising sea level over the period from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0
3

Year Published

1974
1974
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(61 citation statements)
references
References 0 publications
1
57
0
3
Order By: Relevance
“…The ice-movement direction of the last glaciation in Nova Scotia is complex, and, as explained by Prest and Grant (1969), this complexity is probably related to a prolonged period of late, active ice flow from local centres in the Maritimes. They concluded that loc(ll ice caps may have formed in some Maritime areas prior to the advance of the continental ice sheet and that during glacier recession local ice activity was resumed with ice flow in diverse directions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ice-movement direction of the last glaciation in Nova Scotia is complex, and, as explained by Prest and Grant (1969), this complexity is probably related to a prolonged period of late, active ice flow from local centres in the Maritimes. They concluded that loc(ll ice caps may have formed in some Maritime areas prior to the advance of the continental ice sheet and that during glacier recession local ice activity was resumed with ice flow in diverse directions.…”
Section: Discussionmentioning
confidence: 99%
“…The terminal zone of the glacier would then form a topographic high which, bordering the ocean, would provide an area of excessive accumulation analogous to the situation which Prest and Grant ( 1969) postulated for the uplands of south-western Nova Scotia and elsewhere in the Maritimes. Under these conditions, there could have been a short period when the ice reversed its direction of flow until the continuing rise of sea-level dissipated the ice.…”
Section: Discussionmentioning
confidence: 99%
“…Research primarily during the last ten years has demonstrated that much of the Laurentide ice sheet in southern Québec, Maine, and portions of the Maritime Provinces was a "marine-based ice sheet," that is, it was an ice sheet grounded below the prevailing sea level (PREST and GRANT, 1969;BORNS, 1973;STUIVER and BORNS, 1975).…”
Section: Current Understandingmentioning
confidence: 99%
“…12,750 y BP (BROOKES 1974) or the Ten Mile Lake event ca. 11,000 y BP (GRANT, 1969). Locally diamictons spread downslope over pre-existing postglacial organic accumulations, such as the peat dating 10,250 ± 250 y BP (Y-762) on Port Hood Island (TERAS-MAE, 1974) and the peat dating 10,300 ± 150 y BP (GSC-1578) near East Bay (GRANT, 1975a).…”
Section: Inferred Quaternary Eventsmentioning
confidence: 99%
“…Incidental to studies of recent sea-level change, observation of glacial features yielded new evidence for an ice cap over southern Nova Scotia, and for a complex ice-flow sequence over southern Cape Breton (GRANT, 1967(GRANT, , 1968. Preparation of the Glacial Map of Canada (PREST, GRANT and RAMPTON, 1968) afforded an opportunity to examine airphotos of the entire region and this, together with a review of existing ice-flow data, culminated in a hypothesis that the topography and maritime setting prevented and confined the penetration by Labradorean ice, and promoted the growth and determined the retreat pattern of upland and lowland ice caps (PREST and GRANT, 1969).…”
Section: Glacial Stylementioning
confidence: 99%